2018
DOI: 10.2965/jwet.17-040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Magnetic Nanoparticles as a Candidate Draw Solution for Forward Osmosis

Abstract: Synthesis of magnetic nanoparticles (MNPs) attracted the interest of many researchers for many applications. Among the applications of interest is their potential use as a draw solution in forward osmosis owing to their ease of recovery and surface-area-to-volume ratio. Such a draw solution is expected to generate high osmotic pressure. However, for such an application, the choice of coating material is a crucial parameter which is still poorly understood. In this paper, we tested three different coating mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The water flux measured in the experiment was 1.98 LMH which is close to the predicted value of 2.06 LMH. The water flux of the synthesized bare iron oxide nanoparticles was low compared to the water flux obtained when using stabilized iron oxide nanoparticles [33][34][35]. Therefore, it is expected to obtain high water flux when stabilizing the optimized bare iron oxide nanoparticles that were synthesized in this study.…”
Section: Optimization and Model Validationmentioning
confidence: 83%
“…The water flux measured in the experiment was 1.98 LMH which is close to the predicted value of 2.06 LMH. The water flux of the synthesized bare iron oxide nanoparticles was low compared to the water flux obtained when using stabilized iron oxide nanoparticles [33][34][35]. Therefore, it is expected to obtain high water flux when stabilizing the optimized bare iron oxide nanoparticles that were synthesized in this study.…”
Section: Optimization and Model Validationmentioning
confidence: 83%
“…Among these, a relatively small number of studies were evaluated for long operation times (>4 h), all of which observed significant flux decline (up to 50%) due to membrane blocking (from the draw side) 10,13 . For the regeneration/recovery of IONPs, most studies also observed aggregation, which also contributes to flux decline 8,12,[16][17][18] . For all, IONPs aggregation and deposition on the surface of membrane (blocking) remains a critical challenge for effective, long term operation.…”
Section: Introductionmentioning
confidence: 99%